HEGEMONY IN UNTOUCHABLE BY MULK RAJ ANAND - Lovenna Theresia Parapat; Anselmus Chartino Ade (Muse: Jurnal of Art, 2025)
This study aims to analyze the social hierarchy and marginalization in Mulk Raj Anand's Untouchable through the theory of Cultural Marxism, especially Antonio Gramsci's concept of hegemony. This study uses a qualitative narrative method with a descriptive approach. The method used is descriptive qualitative. Data collection was conducted through several steps, namely reading and understanding the novel thoroughly, noting relevant quotations, collecting supporting theoretical references, and classifying the data into categories. Data analysis used the Miles and Huberman framework, which includes data reduction, data display, and conclusion drawing. The results of the study show that the social hierarchy in the novel is reflected through the caste system that places the main character, Bakha, as an "untouchable." Marginalization is seen in the restrictions on Bakha's access to education, work, health services, and places of worship. Hegemony is formed through the dominance of ideology and cultural institutions that make injustice accepted as normal, even by those who are oppressed. This study shows that Untouchable not only depicts social inequality, but also makes readers aware of how ideology works to maintain an unequal power structure. Through this study, readers are expected to be more critical of social injustice that is hidden in culture and social systems.